Shifting the Meaning of Husband’s Maintenance Standards in Islamic Law: A Normative-Empirical Study of Nafaqah Content on Tiktok - Sabila Azza Asyhari; Ruston Kumaini (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Maintenance standards in Islamic law are not fixed or universal, but are determined proportionally according to the husband’s financial capacity and the wife’s essential needs through the principle of bil ma’ruf. The Compilation of Islamic Law reinforces this principle by emphasizing that maintenance must be adjusted to the husband’s ability. However, TikTok content has shifted public perceptions of nafaqah through digital social construction, where nominal figures such as Rp15 million are repeatedly presented as universal standards. This shift changes the understanding of justice from contextual proportionality to nominal equality and reduces qiwamah from a moral and spiritual responsibility into a transactional financial benchmark. Nevertheless, some public responses still reflect the principle of bil ma’ruf, indicating that Islamic legal values remain relevant within digital discourse. This study concludes that the primary challenge lies not in rising living costs, but in the dominance of viral social media narratives that detach maintenance standards from actual financial realities. Therefore, strengthening Islamic legal literacy through contextual digital education and family deliberation is essential to preserve balanced, realistic, and just understandings of maintenance in contemporary Muslim society. Future studies should further examine the long term influence of digital culture on Muslim family legal consciousness in Indonesia.